Effect of Yoga on Depression Levels in Older People Living in Nursing Home - Ghitapenny, Gabriella Astrid; Lilis, Lilis; Ayu, Astri Parawita (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Older people, especially those living in nursing homes, have a higher risk of experiencing depressive disorders. This condition may lead to decreased physical health, decreased social and cognitive function, and increased risk of suicide attempts. One intervention to help the older people overcome depression is yoga. This study aimed to assess the effect of yoga on depression level in older people living in nursing homes. Methods: This study applied a one-group pre-and post-test design. The Geriatric Depression Scale–15 (GDS-15) was used to measure depression levels. Participants were recruited from one of the nursing homes in Jakarta, Indonesia. Yoga intervention was performed directly in the nursing home 3 times a week for 9 weeks with each practice duration of 40 minutes. The paired t-test was used to evaluate the statistical difference in depression scores between pre-and post-intervention. Result: There were 29 out of a total of 68 residents were interviewed after the inclusion and exclusion study was conducted, resulting in 18 respondents who experienced depression and participated in yoga intervention. The majority respondents had mild depression (10 of 12). There was a significant difference in depression scores before and after doing yoga activities (t=11; p<0.001).Conclusion: Yoga can be an effective intervention to reduce depression among older people in nursing homes and yoga as a form of physical activity for the elderly may improve their wellness and enhance quality of life.